Avaliação do impacto do reúso de águas na alocação hídrica dos reservatórios estratégicos da bacia do rio Acaraú, Ceará - Gondim, Ronner Braga (2018)
The intensification of water scarcity threatens billions of people in various parts of the world, forcing them to concentrate in regions with greater water infrastructure, increasing the anthropic impacts of their surroundings and aggravating the spatial heterogeneity. This movement has increased the challenge of providing water more efficiently and has required more sophisticated water resource management models. The management of Northeastern semi-arid reservoirs should be given greater attention because of their strategic importance in guaranteeing the water supply for multiple uses. The high loss of water by evaporation and infiltration on the surface of the reservoirs and in the water transposition are important processes that reduce the efficiency of water supply. Therefore, it is imperative that models of water resources management be supported by efficient hydrological and allocation models. Generally, the return of the wastewater generated by the multiple demands to the water bodies is disregarded in the models, that is, the indirect reuse is ignored, which increases the inflow of downstream reservoirs, tending to make the models more pessimistic. The presence of industrial poles and irrigated perimeters in the Ceará basins also creates the possibility of direct reuse of wastewater for non-potable purposes, which would reduce the consumption of surface water and increase the stock of the reservoirs for human and animal supply. The objective of this study is to evaluate the quantitative impact of direct and indirect water reuse on the water allocation of the strategic reservoirs of the Acaraú River basin, taking into account the 90% Q90 flow limit in Ceará State. VYELAS (Volume-Yield Elasticity) Model was used to quantify the maximum allowable water flowrate, WASA (Water Availability in Semi-Arid Environments) model as a hydrological model for the runoff generation and SIGA (Information System for Water Allocation Management) as a tool of operational simulation of the reservoirs and water allocation. Comparing the results of the scenarios with and without water reuse, it was possible to verify that, in the majority of cases, the inclusion of direct and indirect reuse resulted in a low impact on the strategic reservoirs reliability, in the range of 0.2 to 1.7%. However, the importance of water reuse becomes evident when analyzing the drought period of 2012-17, with an average contribution of between 3.3 and 18%, and a maximum of between 9.2 and 71.2%, for indirect reuse. Adding the direct reuse, the average contribution varied from 9.4 and 18%, and the maximum contribution of 21.7 and 71.2%. The proposed reuse project in the Sobral region has the potential to fully meet its industrial and agricultural demands with an estimated cost of R$ 52 million and flowrate of 265 L/s.